Keeping the lights on : power sector reform in Latin America - Millán, Jaime; Fehr, Nils-Henrik M. von der (Inter-American Development Bank Ser., 2003)
Annotation Power sector reforms across Latin America in the 1990s based on privatization, liberalization and market forces were largely unavoidable. This book argues that while there is no turning back from this process, many reforms may not prove sustainable without further efforts to build a stronger institutional platform to support them. The analytical framework presented in "Keeping the Lights On: Power Sector Reform in Latin America" establishes a baseline for the sustainability of reforms and identifies additional areas for exploration, analysis and inquiry. This analysis is critical to setting the stage for the next generation of reforms -- or mid-course corrections -- that will be necessary to enhance the sustainability of changes in progress. The book includes case studies of power sector reforms in Colombia, Honduras and Guatemala, as well as a timely section on the security of supply.